2018
DOI: 10.1103/physrevd.98.104061
|View full text |Cite
|
Sign up to set email alerts
|

Testing modified gravity theory in the Milky Way

Abstract: We perform a test of John Moffat's Modified Gravity theory (MOG) within the Milky Way, adopting the well known "Rotation Curve" method. We use the dynamics of observed tracers within the disk to determine the gravitational potential as a function of galactocentric distance, and compare that with the potential that is expected to be generated by the visible component only (stars and gas) under different "flavors" of the MOG theory, making use of a state-of-the-art setup for both the observed tracers and baryoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
8
0
3
Order By: Relevance
“…Moreover, this theory can predict successfully the motion within globular clusters, and clusters of galaxies [24,25,26] as well as the rotation curves of spiral and dwarf galaxies [27,28]. Nevertheless, some of us recently showed that the MOG theory is not able to explain the observed rotation curve of the Milky Way [29]. Moreover, when analyzing the Bullet cluster data [30], there are different claims in the literature: some authors affirm that MOG cannot account for them [22] while others hold that its predictions can fit data from both the Bullet and the Train Wreck merging clusters [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this theory can predict successfully the motion within globular clusters, and clusters of galaxies [24,25,26] as well as the rotation curves of spiral and dwarf galaxies [27,28]. Nevertheless, some of us recently showed that the MOG theory is not able to explain the observed rotation curve of the Milky Way [29]. Moreover, when analyzing the Bullet cluster data [30], there are different claims in the literature: some authors affirm that MOG cannot account for them [22] while others hold that its predictions can fit data from both the Bullet and the Train Wreck merging clusters [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Its main problem is the lack of a fundamental acceleration scale, making it extremely difficult to match the observed RAR. As a result, the MW rotation curve is in strong tension with MOG − for any plausible baryonic distribution, the predicted circular velocity at the Solar circle is vc, < 200 km/s (Negrelli et al 2018). However, the observed value is > 200 km/s at overwhelming significance (e.g.…”
Section: Implications For Modifications To Gravity Other Than Mondmentioning
confidence: 96%
“…Se indica en cada caso la masa bariónica de la Vía Láctea calculada de acuerdo a la morfología utilizada y el correspondiente (α, µ) c . Los estimadoresχ 2 equivalentes a 5σ sonχ 2 5σ = 2.41 para la compilación Huang yχ 2 5σ = 1.14 para la compilación galkin (Negrelli et al, 2018 (Negrelli et al, 2018). Figura 4.4.…”
Section: Procedimiento Y Resultadosunclassified
“…Figura 4.4. Curvas de rotación para la teoría MOG considerando los conjuntos de parámetros (α, µ) descriptos en el texto (incluyendo el que da el mejor ajuste, indicado como BF en la figura) para la morfología BF (número 28 de la Tabla 4.4) (Negrelli et al, 2018). a extender el espacio de parámetros independientemente de los valores aceptados dados por las Ecs.…”
Section: Procedimiento Y Resultadosunclassified
See 1 more Smart Citation